The Impact of English Proficiency and Regional Language on Female Students in Indian Higher Education (International Journal of Food and Nutritional Sciences, 2022)
The connection between language and gender is significant, especially within the realm of education. In India, female students hailing from regional language backgrounds encounter distinct obstacles in higher education, particularly in relation to their command of English. In Indian higher education institutions, a notable distinction exists between female and male students, with the former predominantly hailing from regional mediums. This article emphasises the constraints imposed by language barriers on engagements with English-speaking peers and educators, resulting in a sense of inadequacy